Yoga theory and practice - Beach, Leon (New York, NY Syrawood Publishing House, 2019)
Yoga is a set of spiritual, physical and mental practices. It originated in ancient India but is widely practiced throughout the world today. It is an orthodox school of philosophical tradition of Hindu society but has roots in Buddhism and Jainism as well, each of which differs from the other in its philosophical traditions, beliefs and practices. The most famous practices of yoga are Hatha yoga and Raja yoga. Regular practice of yoga is recommended for promoting relaxation, relieving stress and improving medical conditions. It can also act to improve the quality of life for patients suffering from schizophrenia, mental ailments and cancer. This textbook is compiled in such manner, that it will provide in-depth knowledge about the theory and practice of yoga. It outlines the philosophical traditions and schools of yoga and their respective practices in detail. For all those who are interested in practicing yoga, this book can prove to be an essential guide
Understanding yoga and three bodies -- Basic poses of asana -- Pranayama: the control of breathing -- Shatkarma: purification techniques of body --Mudras and bandhas -- Dyhana and meditation
Includes index
Keywords: Yoga -- Therapeutic use; Yoga; Philosophy